Fermentative nutraceuticals - Sindhu, Meena; Panghal, Anil (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2025)
Fermentative Nutraceuticals, the latest volume in the series Bioprocessing in Food Science, presents recent advances and breakthroughs in bioactive peptides derived from fermented foods, highlighting their applications as nutraceuticals. This volume explores opportunities for product design and innovation in food processing. Bioprocessing in Food Science is a series of volumes that comprehensively covers unit operations in food processing. This latest installment addresses the advances, breakthroughs, and challenges associated with fermentative nutraceuticals. The demand for food nutraceuticals and functional foods is growing among consumers worldwide. Academia, researchers, and the food industry are working in a fragmented manner, with technologies developed at each level often not compiled in a unified resource for stakeholders. Typically, the foods we consume are enriched with certain nutrients but deficient in others. Microbial fermentation can enhance the nutritional properties of food. Bioactive peptides produced through fermentation exhibit antioxidative, anticancer, and antidiabetic properties. Increased efforts from the food industry are needed to focus research on peptides and their applications as food-grade preservatives and functional food ingredients. This groundbreaking volume provides a comprehensive compilation of existing research, practical applications, and future research prospects. The editors and contributing experts have made an earnest effort to include every possible detail, presenting an up-to-date repository of scientific literature and their own research findings. This volume is an invaluable resource for students, researchers, product developers, and industry professionals.
Keywords: Functional foods.; Fermented foods.; elektronické knihy; electronic books